Ageing Population's Impact on Economic Growth in Malaysia From 1981 to 2019: Evidence From an Autoregressive Distributed Lag Approach - Mohd, Siti Nur Ain; Ishak, Ayunee Anis; Selvaratnam, Doris Padmini (Frontiers in Public Health, 2021)
This paper attempts to investigate the impact of the ageing population on the economic growth for the short-run and long-run estimations in Malaysia by using time series data that covers the period of 1981-2019. This study adopts the Autoregressive Distributed Lag (ARDL) method with the Bound test approach for long-run estimation and Vector Error Correction Model (VECM) for short-run estimation. Several econometric diagnostic tests were applied for validation and appropriate model specification basis. The estimated result of this study indicates that the age dependency ratio proxy for the ageing population variable has a significant negative impact on economic growth in Malaysia. Meaning that an increase in the ageing population will impede economic growth. While controlled variables such as physical capital, labor participation and human capital have a significant positive impact on economic growth in Malaysia. There is evidence of a long-run and short-run relationship between economic growth and ageing population variable as well as the control variable.